ANALISIS KINERJA BIAYA PADA PROYEK REHABILITASI DRAINASE DAN TROTOAR JALAN TEUKU UMAR PAKET I DENGAN METODE EARNED VALUE - Akhmat Kosbiamtoro; Sugiyanto Sugiyanto (Badan Perencanaan Pembangunan, Riset dan Inovasi Daerah Kabupaten Sragen, 2022)
This research was conducted with the aim of analyzing cost performance in the Drainage and Sidewalk Rehabilitation Project of Jalan Teuku Umar Package I in Tuban Regency, East Java. The earned value method is used in project implementation by involving variables/indicators/indexes consisting of BCWS, BCWP, ACWP, CV, SV, CPI and SPI. The results of the analysis were obtained in the reporting period of the 1st to 13th weeks, the value of the cost variance indicator resulted in a positive value calculation in the sense that cost management could result in cost savings of Rp. 76,988,677 or equivalent to 5.3% of the total budget (cost underrun). Furthermore, based on the results of the calculation of the schedule performance index value, it can be informed that project implementation can be completed on schedule, although in the reporting period of the 4th to 12th week the intensity the project had lagged its progress from the planned schedule.